Bronchial oncocytoma - Aquino, Renata Telles Rudge de (2000)
CONTEXT: Oncocytomas are generally small and present slow growth. Finding of the tumor usually occurs incidentally. Their incidence is higher among male patients. Oncocytomas in mucous bronchial glands are extremely rare. CASE REPORT: A 35-year-old male who presented bronchial oncocytoma. The tumor was found after bronchoscopy that investigated an atelectasis of the upper left lobe. Histological examination with optical microscopy revealed a mature neoplasm formed by ovoid cells with thin, granular, eosinophilic cytoplasm and small nuclei similar to oncocytes. Electron microscopy showed mitochondrial hyperplasia. A three-year follow-up after thoracotomy followed by lobectomy and removal of the bronchial tumor was uneventful.